Numerical analysis on reinforcement ratio of RC beams using FRP and steel rebars - Hemalatha K.; Prasad D. Ravi (E3S Web of Conferences, 2023)
Reinforced Concrete Structures, traditionally using steel rebars, are vulnerable to corrosion under severe exposure conditions. This can result in several drawbacks such as concrete deterioration, reduced serviceability, increased maintenance costs, and reduced structural durability. To counter these issues, Fibre Reinforced Polymer bars have emerged as another possibility material for steel bars. FRP bars are anti-corrosive, have high tensile strength, weigh one-fourth of steel bars, and have a low thermal expansion coefficient similar to concrete. To enhance both load-carrying capacity and ductility, a combining steel bars and FRP bars has been effectively used because FRP bars are having brittle behaviour. This paper studies theoretical investigations of Reinforcement ratio when Fiber Reinforced Polymer bars and steel bars are used as reinforcement in Concrete beams with Af to As as 1 which balance both Flexural capacity and ductility.